Making Sense of Commercial Common Sense - Robertson, Suzanne (Victoria University of Wellington Law Review, 2018)
The article examines the use of "commercial common sense" in the interpretation of commercial contracts. It reviews the origins of the test of commercial common sense and traces the application of the test in relatively recent New Zealand and United Kingdom appellate decisions. The author's contention is that the test is only properly applied when a court asks itself which of the interpretations put forward by the parties is most consistent with the contracting parties' mutual commercial purpose. The test is not properly applied when a court prefers one interpretation to another simply because it is the court's view that the alternative would mean one party made a particularly bad bargain.